Detection of chromium and mercury in water using rGO incorporated Cu-based nanomaterials - Moremi, Harold (My University, 2024)
Heavy metal ions can build up for years or even decades in a number of body organs. Heavy metal poisoning symptoms have the potential to be fatal and to cause permanent harm. According to the United States Environmental Protection Agency (EPA), heavy metals such as chromium, nickel, cadmium, copper, lead, mercury, and arsenic are classified as the most toxic, hence it is important to be able to find simple, rapid methods to detect them in either wastewater or drinking water. In this research study, Cu-based nanomaterials on reduced graphene oxide (RGO) are prepared and then used as an electrocatalyst for the detection of chromium(III) and mercury(II). Copper oxide (CuO) and copper sulfide (CuS) nanoparticles (NPs) were prepared using co-precipitation method and chemical reduction method, respectively. Copper chloride dihydrate (CuCl2.2H2O) was employed as a metal source in both methods. In the case of copper sulfide nanoparticles, thioacetamide (TAA) was employed as the sulfur source in the presence of GSH (Glutathione), which was employed as a capping agent. Both CuONPs and CuSNPs were also coated with Gold (Au) to form polyhedral hetero-structure composed of both gold nanoparticles and CuO nanoparticles. The prepared CuO, CuS, CuO-Au and CuS-Au were then incorporated on RGO using different chemical processes in order to produce CuO/RGO, CuS/RGO, CuO-Au/RGO and CUS-Au/RGO nanocomposites. All prepared nanoparticles and nanocomposites were characterized with ultraviolet visible (UV-Vis) spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM), fourier-transform infrared (FTIR) microscopy and Raman spectroscopy. In addition, glassy carbon electrodes (GCEs) modified with CuO, CuS, CuO-Au, CuS-Au CuO/RGO, CuS/RGO, CuO-Au/RGO and CUS-Au/RGO were prepared, and the electrochemical activities of each modified electrode were investigated using the [Fe(CN)6]3-/4- probe via cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). CuS-Au/RGO exhibited high electron transfer with low resistance charge transfer (Rct) by EIS analysis. Therefore, was chosen as the material of interest during the development of the electrochemical sensor for both Cr(III) and Hg (II) heavy metal ions. The sensor parameters such as scan rate, pH and deposition potential and time were optimized. The CUS-Au/RGO showed good stability and reactivity at pH of 6.17. The fabricated sensor exhibited very low detection limits of 2 ppb for Hg(II) and 2 ppb for Cr(III). However, the CuS-Au/RGO nanocomposite based electrochemical sensor evidently demonstrated to have a strong binding affinity and preference for Hg(II) than Cr(III)
Thesis (M. Sc. (Chemistry)) -- University of Limpopo, 2024
Keywords: Chromium; Ions; Copper; Wastewater; Nanoparticles; Mercury; Chromium; Water -- Mercury content; Metal ions